Impact of optical current transformer on protection scheme of hybrid transmission line - Zainal Arifin; Muhammad Zulham; Eko Prasetyo (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Continuity of power transmission is important to ensure the reliability of the electricity supply. As most system faults are temporary, the auto reclose (AR) scheme has been used extensively to minimise the outage duration, prevent widespread outages, thus increase system stability. Meanwhile, the hybrid transmission line (HTL) combining overhead line (OHL) and high voltage cable has been introduced to provide an inexpensive solution for an urban power grid. Protecting HTL with a conventional protection system would forbid the operation of the AR scheme due to difficulty to ensure whether the fault occurred on the OHL or cable section. Therefore, the circulating current protection (CCP) scheme is used in the cable section to ensure the fault location and block the AR scheme. The technology of an optical current transformer (OCT) as one of the non-conventional instrument transformers (NCIT) has emerged to provide a solution to drawbacks on the conventional current transformer (CCT). Consequently, this paper investigated the impact of using OCT over the CCT for CCP of the HTL. The result shows that OCT could be used for CCP on much longer cable sections thus increase its reliability as the AR scheme can be used on longer or multiple cable section.